2021
DOI: 10.1073/pnas.2011226118
|View full text |Cite
|
Sign up to set email alerts
|

NAD + supplementation reduces neuroinflammation and cell senescence in a transgenic mouse model of Alzheimer’s disease via cGAS–STING

Abstract: Alzheimer's disease (AD) is a progressive and fatal neurodegenerative disorder. Impaired neuronal bioenergetics and neuroinflammation are thought to play key roles in the progression of AD, but their interplay is not clear. Nicotinamide adenine dinucleotide (NAD+) is an important metabolite in all human cells in which it is pivotal for multiple processes including DNA repair and mitophagy, both of which are impaired in AD neurons. Here, we report that levels of NAD+ are reduced and markers of inflammation incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
185
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 278 publications
(195 citation statements)
references
References 61 publications
10
185
0
Order By: Relevance
“…Increased deposition of amyloid plaques extracellularly and accumulation of hyperphosphorylated tau proteins intracellularly are two pathological hallmarks of Alzheimer's disease [44,45]. Although the mechanisms underlying increased deposition of Aβ and phosphorylated tau proteins in the brain of LOAD patients are unknown, several mouse models that overexpress mutant human amyloid precursor protein (APP) or APP plus mutant human presenilin 1 or mutant form of human microtubule-associated protein tau P301S have been generated and used to study the mechanisms, whereby Aβ and hyperphosphorylated tau proteins promote AD pathophysiology [24,25,40,41,49,[70][71][72][73][74][75][76]. Emerging evidence from these animal studies indicates that increased Aβ and tau phosphorylation promote brain cell senescence and that cellular senescence plays a critical role in the neuropathology and memory decline in AD.…”
Section: Evidence Of Cellular Senescence In Ad Model Micementioning
confidence: 99%
See 3 more Smart Citations
“…Increased deposition of amyloid plaques extracellularly and accumulation of hyperphosphorylated tau proteins intracellularly are two pathological hallmarks of Alzheimer's disease [44,45]. Although the mechanisms underlying increased deposition of Aβ and phosphorylated tau proteins in the brain of LOAD patients are unknown, several mouse models that overexpress mutant human amyloid precursor protein (APP) or APP plus mutant human presenilin 1 or mutant form of human microtubule-associated protein tau P301S have been generated and used to study the mechanisms, whereby Aβ and hyperphosphorylated tau proteins promote AD pathophysiology [24,25,40,41,49,[70][71][72][73][74][75][76]. Emerging evidence from these animal studies indicates that increased Aβ and tau phosphorylation promote brain cell senescence and that cellular senescence plays a critical role in the neuropathology and memory decline in AD.…”
Section: Evidence Of Cellular Senescence In Ad Model Micementioning
confidence: 99%
“…These mice display a significant increase in brain Aβ load and memory impairment and have been widely used as a murine model of familial AD. Emerging evidence shows that various types of brain cells, including oligodendrocyte precursor cells (OPCs), astrocytes, microglia, and neurons, express higher levels of senescence markers p16, p21, and SA-β-gal in these familial AD model mice [25,40,70,71] Nicotinamide adenine dinucleotide (NAD+) is an important metabolite and is involved in many biological processes. Hou et al reported that, associated with a decline in NAD+ level in the brain, various types of brain cells in APP/PS1 mice displayed a senescence phenotype, including increased SA-β-gal activity, as well as increased p16 and p21 expression, [71].…”
Section: Mice Overexpressing Amyloid Precursor Protein (App)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, such studies may provide useful mechanistic insights to develop therapeutic opportunities against inflammation in aging and in age-related disorders. Indeed, evidence is emerging that the cGAS-STING pathway is malleable to modification by pharmacological intervention [ 226 ].…”
Section: Discussionmentioning
confidence: 99%